Organic emissions from coal pyrolysis: mutagenic effects. - Braun, A G (1987)
Four different types of coal have been pyrolyzed in a laminar flow, drop tube furnace in order to establish a relationship between polycyclic aromatic compound (PAC) evolution and mutagenicity. Temperatures of 900K to 1700K and particle residence times up to 0.3 sec were chosen to best simulate conditions of rapid rate pyrolysis in pulverized (44-53 microns) coal combustion. The specific mutagenic activity (i.e., the activity per unit sample weight) of extracts from particulates and volatiles captured on XAD-2 resin varied with coal type according to the order: subbituminous greater than high volatile bituminous greater than lignite greater than anthracite. Total mutagenic activity (the activity per gram of coal pyrolyzed), however, varied with coal type according to the order: high volatile bituminous much greater than subbituminous = lignite much greater than anthracite, due primarily to high organic yield during high volatile bituminous coal pyrolysis. Specific mutagenic activity peaked in a temperature range of 1300K to 1500K and generally appeared at higher temperatures and longer residence times than peak PAC production.